2016
DOI: 10.4236/oalib.1102374
|View full text |Cite
|
Sign up to set email alerts
|

Study Effect of Powder Protein Intake on Total Protein and Creatinine Concentrations in Blood of Bodybuilder

Abstract: The powder protein is mostly used as the main dietary by bodybuilders for improving exercise training. This research studied the effect of the powder protein intake on serum total protein and creatinine concentrations, and urine pH and protein of three different groups. The serum total protein concentration has no relationship with the amount of powder protein intake and cannot be affected by it. But the serum creatinine concentration has a direct relationship with the amount of powder protein intake. The grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The protein intake of the athletes interviewed seemed to increase with their competitive commitment; in fact, protein intake increased and became the only food intake of bodybuilders during competitive periods. Our study confirmed that bodybuilders generally eat more than the recommended intake (Chauliac 2015) and adopt high-protein diets (e.g., Helms, Aragon, and Fitschen 2014;Monteiro, Pimentel, and Sousa 2012;Omar, Othman, and Ismail 2016) and that such tendencies increase along with competitive commitment. Moreover, the increased frequency of food intake seemed to have negative consequences, such as night eating syndrome.…”
Section: Deviant Behaviors Emerging With the Intention To Compete Andsupporting
confidence: 79%
See 2 more Smart Citations
“…The protein intake of the athletes interviewed seemed to increase with their competitive commitment; in fact, protein intake increased and became the only food intake of bodybuilders during competitive periods. Our study confirmed that bodybuilders generally eat more than the recommended intake (Chauliac 2015) and adopt high-protein diets (e.g., Helms, Aragon, and Fitschen 2014;Monteiro, Pimentel, and Sousa 2012;Omar, Othman, and Ismail 2016) and that such tendencies increase along with competitive commitment. Moreover, the increased frequency of food intake seemed to have negative consequences, such as night eating syndrome.…”
Section: Deviant Behaviors Emerging With the Intention To Compete Andsupporting
confidence: 79%
“…Bodybuilders eat large amounts of proteins (Helms, Aragon, and Fitschen 2014;Monteiro, Pimentel, and Sousa 2012) because studies have highlighted the benefits of high-protein diets for weight loss (e.g., Gentil 2015). Bodybuilders use also supplementation, such as powder proteins, containing "important nutrients for building and maintaining all types of body parts including muscles, bones, hair, and nails" (Omar, Othman, and Ismail 2016). Powder proteins are very popular supplements among bodybuilders to aid in muscle development (Bianco et al 2011;Omar, Othman, and Ismail 2016), and coaches are the main source of information on intake supplementation (Bianco et al 2011).…”
Section: Alimentation Supplementation and Doping Use In Bodybuildersmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect to our results, previous study illustrated that the taking the nutritional protein not related to the serum total protein and nutritional protein taking exert no influences on the level of total protein in the sera. However, the supplement protein taking was positively correlated with the level of serum creatinine (Omar et al, 2016). Therefore, current study concluded that the nutritional supplements users are need to ingest an appropriate quantity of protein till the level of serum creatinine back to standard scale to stop any defect might occur to their kidneys.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, current study concluded that the nutritional supplements users are need to ingest an appropriate quantity of protein till the level of serum creatinine back to standard scale to stop any defect might occur to their kidneys. It reported that the protein taking in low and/or high amount over a period of the time has a negative impact on the renal system of physically active individuals and non-active one (Omar et al, 2016).The main liver-obtained plasma protein is albumin which is not troubled via strength physical activity in younger individuals (Sheffield- Moore et al, 2005). Nevertheless, the present of a large amount of amino acids will be enhancing the albumin protein production (Caso et al, 2007).…”
Section: Resultsmentioning
confidence: 99%